Benefits of Non-Invasive Mechanical Ventilation (NIMV) in the postoperative period of Myocardial Revascularization Surgery (MRS): Integrative review (Research, Society and Development, 2024)
Cardiovascular disease is one of the main causes of hospital admission in Brazil, mainly affecting people with high blood pressure as a risk factor. However, in Brazil, the mortality rate after Myocardial Revascularization Surgeries is higher than in countries such as the United States and Canada, due to the high prevalence of cardiovascular risk factors in the Brazilian population. Objective: The present study aims to verify the benefits of using NIMV in the postoperative period of CABG. Methods: Research was carried out in the databases: LILACS, PUBMED, AND PEDRO for the years 2013 to October 2023; where 1202 articles were found, in which the inclusion criteria corresponded to articles available in full, randomized controlled clinical trial (RCT), in Portuguese and English, which addressed the adult population and who underwent CABG. Results: 10 RCTs involving 1287 patients were part of this study, 1090 of which were allocated to groups containing NIMV techniques, compared to conventional exercises or other techniques, predominantly male, with some groups containing an average of two sessions per day with an estimated time of 25 -30 min. Conclusion: This integrative review study showed that the applicability of NIMV in the postoperative period of CABG is effective in promoting greater exercise tolerance, improving functional capacity, and regulating cardiac autonomic automation, which reduces postoperative complications, resulting in a shorter length of stay, as well as a lower cost per capita in health.